FINANCIAL LITERACY – AN ESSENTIAL LIFE SKILL IN TODAY’S SOCIETY - SANDRA TEODORESCU (Challenges of the Knowledge Society)
Financial education is a concept that emerged nearly 200 years ago, namely in the 18th century. Its role grew rapidly in the 20th and 21st centuries. It is centered around concepts such as budgeting and saving, integrated into financial education programs, aimed both at explaining salary management mechanisms and at presenting financial protection mechanisms and long and medium-term investment tools. Financial literacy is not just a trend, but an essential life skill in today’s society, which enable us to develop and balance our budget, make more appropriate short and long-term saving decisions, and select the best financial products that could make life easier for us.